Pollen calendar to depict seasonal periodicities of airborne pollen species in a city situated in Indo-Gangetic plain, India. (1st October 2021) - Ravindra, Khaiwal; Goyal, Akshi; Kumar, Sahil; Aggarwal, Ashutosh; Mor, Suman
Abstract: The growing incidences of asthma, allergic rhinitis/hayfever, and other pollen-associated allergenic diseases have become an important issue in recent years. A qualitative and quantitative evaluation of airborne pollen in Chandigarh was conducted during 2018–2020 using a Burkard volumetric-spore sampler. The Annual Pollen Integral (API) was 21, 244 pollen grains/m 3 in 2018-19 and 20, 412 pollen grains/m 3 in 2019-20, belonging to 74 pollen types. The greatest annual mean pollen percentage for 2018–2020 was attributed to Morus alba (66.74%) followed by Poaceae (6.55%), Cannabis sativa (6.74%), Celtis occidentalis (2.25%), Parthenium hysterophorus (1.51%), Eucalyptus sp. (1.37%) and remaining pollen types represented 14.84% altogether. The highest pollen concentrations were observed from February to April, corresponding to the pollen taxa seasonality that mainly contributes to the local airborne pollen spectrum. The airborne pollen calendar of Chandigarh depicts seasonal periodicities. The annual cycle shows two main seasons, i.e., a spring season dominated by arboreal pollen types ( Celtis occidentalis, Eucalyptus sp., Morus alba and Pinus sp.) and autumn season dominated by herbs (Amaranthaceae/Chenopodiaceae, Cannabis sativa and Poaceae). The magnitude of start and end dates with season-length for key species were also observed, showing substantial higher pollen concentration and longer seasons length over a period of two years in Chandigarh. This seems to be linked with their extended reproductive cycle and the flowering period, including the impact of inter-year climatic variations. Identifying key allergic species and their pollen-releasing seasons, including the development of the pollen calendar, will be useful to develop strategies to reduce the impact of pollen allergy for susceptible individuals. Graphical abstract: Image 1 Highlights: The main airborne pollen dominating seasons were spring and autumn, with maximum species. The Annual Pollen Integral was over 20, 000 pollen/m 3 belonging to 74 pollen types. Morus alba and Poaceae were the most abundant pollen types present throughout both years. Many of the pollen types found are considered allergy-causing pollen producers in India. First pollen calendar for the city of Chandigarh has been developed to help susceptible individuals and allergy specialists.